Pulmonary artery pressures and outcomes after MitraClip. (21st October 2020) - Rashi, Yonatan; Haberman, Dan; Tonchev, Ivaylo; Peretz, Alona; Medvedovsky, Anna Turyan; Gotsman, Israel; Minha, Saar; Poles, Lion; Shimoni, Sara; Goland, Sorel; Perlman, Gidon Y.; Danenberg, Haim D.; et al.
Abstract: Aims: We evaluated the impact of MitraClip on systolic pulmonary artery pressure (sPAP) and the effects of baseline sPAP on outcomes. Methods and results: In a cohort of patients who underwent MitraClip implantation, three groups were defined according to pre‐procedure sPAP levels. Clinical and echocardiographic data were compared. The study included 177 patients: 59 had severe pulmonary hypertension (PHT), 96 had mild to moderate PHT, and 22 had no PHT. In patients with pre‐existing severe PHT, sPAP was reduced from 70.8 ± 9.2 to 56.8 ± 13.7 mmHg ( P  < 0.001), sPAP remained unchanged in patients with mild to moderate PHT but was significantly increased from 30.8 ± 4.3 to 38.6 ± 8.3 mmHg in the no‐PHT group ( P  < 0.001). Improvement of sPAP was observed in 77% of severe PHT group, while worsening of sPAP was more common among patients with no‐PHT [57% compared with 33% among the mild to moderate PHT and 7% in the severe PHT group, respectively, ( P  < 0.001)]. One year survival was similar among the study groups. Conclusions: MitraClip decreases PHT among patients with severe PHT. A concerning finding is that most patients with no‐PHT increase their sPAP.